Testing for Structural Breaks in the Presence of Data Perturbations: Impacts and Wavelet Based Improvements - Simon Reese; Yushu Li (Lund University, School of Economics and Management, Department of Economics, 2013)
This paper investigates how classical measurement error and additive outliers influence tests for structural change based on F-statistics. We derive theoretically the impact of general additive disturbances in the regressors on the asymptotic distribution of these tests for structural change . The small sample properties in the case of classical measurement error and additive outliers are investigated via Monte Carlo simulations, revealing that sizes are biased upwards and that powers are reduced. Two wavelet based denoising methods are used to reduce these distortions. We show that these two methods can significantly improve the performance of structural break tests.
Keywords: C11; C12; C15; 330; Structural breaks; measurement error; additive outliers; wavelet transform; empirical Bayes thresholding